2014
DOI: 10.1111/jcmm.12212
|View full text |Cite
|
Sign up to set email alerts
|

Trichostatin A, a histone deacetylase inhibitor, suppresses proliferation and epithelial–mesenchymal transition in retinal pigment epithelium cells

Abstract: The proliferation and epithelial–mesenchymal transition (EMT) of retinal pigment epithelium (RPE) cells are the major pathological changes in development of proliferative vitreoretinopathy (PVR), which leads to severe visual impairment. Histone deacetylases (HDACs)-mediated epigenetic mechanisms play important roles in controlling various physiological and pathological events. However, whether HDACs are involved in the regulation of proliferation and EMT in PRE cells remains unidentified. In this study, we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 35 publications
3
48
0
1
Order By: Relevance
“…Links between the activation of p44/42MAPK, p38 MAPK and AKT signalling and TGF-β2-induced EMT have been previously and recently established [3840]. Crosstalk between these signalling pathways and the Smad-dependent pathway has also been reported [9].…”
Section: Discussionmentioning
confidence: 99%
“…Links between the activation of p44/42MAPK, p38 MAPK and AKT signalling and TGF-β2-induced EMT have been previously and recently established [3840]. Crosstalk between these signalling pathways and the Smad-dependent pathway has also been reported [9].…”
Section: Discussionmentioning
confidence: 99%
“…24 TSA was also reported to suppress cell proliferation and epithelial-mesenchymal transition through inactivation of the component of LPS/TLR4 signaling pathway, such as phosphatidylinositol-3-kinase (PI3K)/Akt, p38 mitogen-activated protein kinase (MAPK), and extracellular signal-regulated kinase(ERK)1/2 pathways. 25,26 Meanwhile, Sato et al 27 reported that inhibition of HDACs with TSA in human choriodecidual explants led to a massive increase in LPS-stimulated interleukin (IL)-1β, indicating that HDACs can also negatively regulate the expression of some target genes. In our present study, by means of TLR4-siRNA- lentivirus infection, we further demonstrated that LPS stimulated the expression and activation of HDAC-4, -5, and -7 through TLR4, implying that the TLR4-mediated expression and activation of HDACs may play an important role in LPSinduced epigenetic regulation of gene expression in lung fibroblasts and phenotype transition.…”
Section: Discussionmentioning
confidence: 99%
“…To make matters more complicated, these noncanonical TGFβ signals and the canonical Smad signaling can also be mediated by other signaling pathways, such as the Notch pathway [9]. In RPE cells, our previous study has demonstrated that ERK1/2 signaling pathway is activated by TGFβ2, however, the role of it has not been elaborated [17].…”
Section: Introductionmentioning
confidence: 99%